PERANAN KOMUNIKASI INTERPERSONAL GURU DALAM MENINGKATKAN PENGETAHUAN ANAK: (Studi pada guru di TK RA Raudhatul Abral) - Raisyaalfitahusna Raisyaalfitahusna; Kamaruddin Hasan (Jurnal Komunikasi dan Budaya, 2024)
This study aims to find out how the comunication process used by teacher in the teaching and learning process. Forms of communication and approaches to communication by teacher to students. This study used a qualitative research method with data collection techniques using observation, in depth interviews, and document studies as well well as descriptive data analisis techniques with presentation. The formulation of the research problem is how in the role of teacher internasional communication in increasing children’s knowledge. Baset on the result of the research and discussion, it can be concluded that the research isbas follow: (1) overall the role of the teacher’s interpersonal communication in increasing children’s knowledge is concluded to be quite good. (2) the language used by the teacher is very appropriate in communicating with their students. (3) non verbal communication carried out by the teacher in interacting with his student is by using gestures, facial expressions and expressions, symbols and various intonation of voice. (4) the message conveyed in teacher studen interpersonal communication are more about the concept of the lessonand also motivation for their students to more quickly understand what the teacher means.